(untitled) (Experimental biology, 2015)
Mycosymbiotrophism study of 24 plant species from nival belt of Titov pass’ eastern slope showed that 71.9 percent of specimens studied were either mildly mycotrophic or non-mycotrophic (37.5 and 34.4 percent respectively). Highly mycotrophic species have not been identified. Average mycorrhizzal infection intensity index was as low as 1.76 points.The frequency of mycorrhizal infection occurrence in examined plants was 64.7 percent.Plants from Asteraceae and Rosaceae displayed the highest rates of mycorrhizal infection intensity. Labiatae, Poaceae,Fabaceae had slightly less intense mycorrization, whereas the lowest infection rates were observed in Saxifragaceae,Caryophylaceae. Non-mycorrhizal species belonged to Papaveraceae, Cruciferae, Cyperaceae families.